A new hybrid filter based on differential current control method for low‐order harmonic suppression in Tokamak power system. (21st July 2017) - Lu, Jing; Fu, Peng; Li, Jun; Mao, Huafeng; Shen, Xianshun; Xu, Liuwei; Wu, Yanan
Summary: With high‐power, high‐parameter operation of Tokamak device, not only characteristic harmonics but also much noncharacteristic harmonics, especially below the third‐order harmonics, present in its power supply system. These low‐order harmonics, which further amplified by the capacitive impedance in system, will endanger the reliable operation of Tokamak device and the power supply. Although Tokamak devices have taken some filtering measures, the resonance of low‐order harmonics could not be completely prevented. In this paper, a hybrid filter based on differential current control method is proposed, which can effectively increase the filtering capability. The hybrid filter was mainly analyzed and validated in EAST power supply system. The results show that it can restrain the resonance and suppress low‐order harmonics in the system and can be extended to large‐capacity occasions.